Digitalization driven retail business model innovation : Evaluation of past and avenues for future research trends - Mostaghel, Rana; Oghazi, Pejvak; Parida, Vinit; Sohrabpour, Vahid (Elsevier, 2022)
Increased digitalization enabled innovation and practical examples from the retail industry have captured the attention of marketing scholars, with rapid development in the academic field. The pace of change has significantly accelerated during the Covid-19 crisis. In seeking to (1) investigate the unique characteristics of digitalization enabled retail business model innovation, (2) understand how does digitalization influences changes to the retail business model innovation dimensions, and (3) identify the areas for future research related to retail business model innovation, this study systematically reviews the literature. Employing four databases, a sample of 170 articles were chosen. Based on bibliometric and network analysis and visualization, the major researchers, articles, and topics were rigorously identified. Finally, the results revealed the unaddressed issues in this research area. The study ends with theoretical and managerial implications.
Keywords: Bibliometric analysis; Innovation; Literature review; Network analysis; Retail business model; fi=Strateginen johtaminen|en=Strategic Management|